Dengue and the risk of urban yellow fever reintroduction in São Paulo State, Brazil Dengue e risco da reintrodução da febre amarela urbana no Estado de São Paulo - Eduardo Massad; Marcelo Nascimento Burattini; Francisco Antonio Bezerra Coutinho; Luiz Fernandes Lopez (Universidade de São Paulo, 2003)
OBJECTIVE: To propose a mathematical method for the estimation of the Basic Reproduction Number, R0, of urban yellow fever in a dengue-infested area. METHODS: The method is based on the assumption that, as the same vector (Aedes aegypti) causes both infections, all the quantities related to the mosquito, estimated from the initial phase of dengue epidemic, could be applied to yellow fever dynamics. It is demonstrated that R0 for yellow fever is, on average, 43% lower than that for dengue. This difference is due to the longer dengue viremia and its shorter extrinsic incubation period. RESULTS: In this study the analysis was expanded to the epidemiological situation of dengue in São Paulo in the year 2001. The total number of dengue cases increased from 3,582 in 2000 to 51,348 in 2001. It was then calculated R0 for yellow fever for every city which have shown R0 of dengue greater than 1. It was also estimated the total number of unprotected people living in highly risky areas for urban yellow fever. CONCLUSIONS: Currently there is a great number of non-vaccinated people living in Aedes aegypti infested area in the state of São Paulo. OBJETIVO: Propor um modelo matemático para a estimativa da reprodutibilidade basal, R0, para a febre amarela urbana em uma área infestada pela dengue. MÉTODOS: O método utilizado considera que, como ambas as doenças são transmitidas pelo mesmo vetor (Aedes aegypti), poder-se-ia aplicar todos os parâmetros quantitativos relativos ao mosquito, estimados pela fase inicial da curva de crescimento de casos de dengue, à dinâmica da febre amarela. Demonstra-se que o R0 da febre amarela é em média 43% menor que o da dengue. Esta diferença deve-se à viremia mais prolongada da dengue, bem como ao menor período de incubação extrínseco daquele vírus no mosquito. RESULTADOS: Apresenta-se a aplicação desta análise matemática à situação epidemiológica da dengue no estado de São Paulo, para o ano de 2001, onde o número de casos de dengue aumentou de 3.582, em 2000 para 51.348, em 2001. Calculou-se o valor de R0 para a febre amarela para cada cidade do estado que tinha R0 para dengue maior que um. Estimou-se o número total de pessoas desprotegidas, sem vacina, e que vivem em áreas de alto risco para a febre amarela urbana. CONCLUSÕES: Foi demonstrado que existe, um grande contingente de pessoas não vacinadas contra febre amarela vivendo em áreas infestadas por Aedes aegypti no Estado de São Paulo, até aquela data (2001).